HOUT-23. ADULT MEDULLOBLASTOMA TREATMENT IMPACT SINCE 2006: A CANADIAN UNIVERSITY CENTER EXPERIENCE. (11th November 2019) - Camila Quinones Ninos, Maria; Belanger, Karl; Lemieux Blanchard, Emilie; Lemieux, Bernard; Bahary, Jean-Paul; G Masucci, Laura; Roberge, David; Menard, Cynthia; Lambert, Carole; Moumdjian, Robert; Berthelet, France; Florescu, Marie
Abstract: INTRODUCTION: Medulloblastoma (MB) is an aggressive primary brain tumor rare in adults. Prospective studies in adults are limited by the small number of patients. METHODS: We retrospectively reviewed all MB patients treated at the CHUM between 2006 and 2017 in our clinical database adult SARDO. We don't have the children follow up. We divided our cohort in 2 groups, those diagnosed between 2006–2013 and those diagnosed between 2014–2017. RESULTS: 49 patients were treated, 23 (47%) were children referred for radiation only from a pediatric center and 26 (53%) were adults. Median follow up of adults was 26 months. At 5 years, the entire cohort OS was 58%, but specifically for adults, the 5yOS was 80%. First line therapy had a 5y PFS 77% for adults, negatively influenced by the absence of adjuvant radiotherapy (83% vs 0%; p < 0.001) and the absence of adjuvant chemotherapy (80% vs 39%; p < 0.008). 96% of adult patients received radiotherapy and 52% of them received concomitant radiosensitizing chemotherapy with no impact on survival. Complete surgical resection was performed on 88% of patients, but the extent of resection did not have an impact on survival and did not change with time. From 2006–2013, the most common chemotherapy treatment (80%) in adults was Vincristine, Cisplatin and Lomustine. From 2014–2017, the chemotherapy was replaced by Cisplatin, Etoposide and Cyclophosphamide in 82% with no impact on survival (specific mortality for this chemo 3yOS 100% for both, 3y PFS 100%). Non Cisplatin based chemotherapy regimens were associated with decrease in PFS (67% at 3y). 78% of the progressive patients received second line chemo. CONCLUSION: In our adult MB population, the demographic and tumor factors did'nt have an impact on prognosis but adjuvant radiotherapy and chemotherapy had a favorable impact on survival especially with Cisplatin, Etoposide and Cyclophosphamide regimen.